Review on Cutting Force Compensation Techniques for Machine Tools Application - Jamaludin, Zamberi; Minhat, Mohamad (2014)
Abstract. This paper reviews compensation methods on effects of disturbance forces on positioning accuracy in linear drives system for machine tools applications. Linear motor is directly subjected to disturbances forces acting in the direction of motion giving rise to the needs for alternative robust controllers in order to ensure precision and high tracking performance. This paper investigates effect of cutting forces generated during milling process on tracking accuracy of a linear drive motor. Recent studies are focusing on design of adaptive compensators that provide robustness against system uncertainties while maintaining high degree of precision and accuracy generally required in high performance machining applications